Long term efficacy of developmentally adapted cognitive processing therapy in youth with abuse related PTSD — Follow-up of a randomized control trial. (October 2022) - Steil, Regina; Weiss, Judith; Rimane, Eline; Renneberg, Babette; Rosner, Rita
Abstract: Background: Adolescents and young adults with abuse-related post traumatic stress disorder (PTSD) have been shown to benefit from Developmentally Adapted Cognitive Processing Therapy (D-CPT), yet long-term efficacy of D-CPT has not yet been studied. Objective: To assess the long-term efficacy of D-CPT in a sample of adolescents and young adults (age 14–21 years) with childhood abuse related PTSD. Participants and setting: Patients of a previously conducted multicenter randomized controlled trial which showed the efficacy of D-CPT compared to a waitlist with treatment advice (WL/TA) were invited for follow-up assessments at 6 and 12 months after the end of treatment. Methods: Primary outcome was the PTSD symptom severity, assessed with the Clinician-administered PTSD Scale for Children and Adolescents (CAPS-CA). Secondary outcomes were self-reported PTSD severity, depression, borderline symptom severity, behavior problems, and dissociation. Results: Of the 44 participants who received D-CPT, 28 (63 %) responded and were assessed at 6-month follow-up. At 12-month follow-up, 22 participants (50 %) responded. The majority of participants in the WL/TA group received D-CPT after the end of the trial and were hence not available for follow-up assessment. In the D-CPT group, treatment gains were maintained at 6- and 12-month follow-up in the CAPS-CA as well as in all secondary outcomes. Conclusions: The positive effects of D-CPT were stable in adolescents and young adults with abuse-related PTSD indicating that they can benefit in the long term from a treatment with D-CPT.